2016
DOI: 10.1038/srep31970
|View full text |Cite
|
Sign up to set email alerts
|

Arterialized Venous Bone Flaps: An Experimental Investigation

Abstract: In arterialized venous flaps (AVFs) the venous network is used to revascularize the flap. While the feasibility of AVFs in soft tissues has been reported there is no study on osseous AVFs. In this study we aim to assess the flap survival of osseous AVFs in a pig model. Medial femoral condyle flaps were elevated in 18 pigs. Three groups were created: AVF (n = 6), conventional arterial flap (cAF, n = 6) and bone graft (BG, n = 6). The AVFs were created by anastomosis of genicular artery with one vena comitans wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…[ See Table, Supplemental Digital Content 2 , which shows the summary of the studies on unconventional perfusion flaps in experimental animal models identified in the systematic review and included in the meta-analysis. 12,17,20,41,43,49-111 For each study, the optimized experimental animal model is identified, along with its characteristics. These experimental models were those that presented better flap survival rates in each published article ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ See Table, Supplemental Digital Content 2 , which shows the summary of the studies on unconventional perfusion flaps in experimental animal models identified in the systematic review and included in the meta-analysis. 12,17,20,41,43,49-111 For each study, the optimized experimental animal model is identified, along with its characteristics. These experimental models were those that presented better flap survival rates in each published article ( p < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Half of the identified articles were published until 1994, and three-quarters of these were published until 2003. Studies were performed in 20 different countries 12,17,20,41,43,49-111 (cited in Table, Supplemental Digital Content 2 , http://links.lww.com/PRS/D415). The most commonly used animal species was the rabbit (57.1 percent), followed by the rat (26.4 percent), the dog (14.3 percent), and the pig (2.2 percent).…”
Section: Resultsmentioning
confidence: 99%
“…To date, animal experimental studies on the MFC flap have been performed only in pigs. In 2016, Borumandi et al studied the long-term impact of arterialized venous bone flaps employed in pig MFC [ 19 ]. In 2018, Higgins et al compared the long-term cartilage quality of vascularized versus nonvascularized osteocartilaginous flaps of the MFC [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the large animals used for TMJ reconstruction research, pigs are the most suitable, since their joint, disc morphology and mandibular movement patterns are similar to those of humans [ 18 ]. Moreover, the vascularized MFC flap has only been studied in miniature pigs [ 19 , 20 ]. In the present study, we developed a miniature pig model of a unilateral vascularized MFC osteocartilaginous flap to regenerate an RCU defect.…”
Section: Introductionmentioning
confidence: 99%